Molecular identification of two thioredoxin genes and their function in antioxidant defense in Arma chinensis diapause - Zhongjian Shen; Qiaozhi Luo; Qiaozhi Luo; Jianjun Mao; Yuyan Li; Mengqing Wang; Lisheng Zhang; Lisheng Zhang (Frontiers in Physiology, 2024)
Thioredoxin (Trx), an important part of thioredoxin systems, plays crucial role in maintaining the intracellular redox balance by scavenging reactive oxygen species (ROS). However, few Trxs have been functionally characterized in Arma chinensis, especially in diapause. In this study, diapause induction condition promoted hydrogen peroxide accumulation and increased CAT enzymatic activity and ascorbate content, suggesting that A. chinensis was exposed to high level of ROS. Therefore, we identified AcTrx2 and AcTrx-like, and investigated the relationship with antioxidant defense. It was found that AcTrx2 expression was significantly induced, whereas AcTrx-like expression was the highest on day 10 under diapause conditions. The expression of AcTrx2 and AcTrx-like in fat body, a central metabolic organ of resisting oxidative stress, was significantly increased under diapause conditions, and was significantly improved by 5/15°C (diapause temperature). We investigated the knockdown of AcTrx2 and AcTrx-like in A. chinensis and found that some selected antioxidant genes were upregulated, indicating that the upregulated genes may be functional compensation for AcTrx2 and AcTrx-like silencing. We also found that the enzymatic activities of SOD and CAT, and the metabolite contents of hydrogen peroxide, ascorbate increased after AcTrx2 and AcTrx-like knockdown. These results suggested the AcTrx2 and AcTrx-like may play critical roles in antioxidant defense of A. chinensis diapause.